Technical note: Evaluation of a V‐Net autosegmentation algorithm for pediatric CT scans: Performance, generalizability, and application to patient‐specific CT dosimetry - Adamson, Philip M.; Bhattbhatt, Vrunda; Principi, Sara; Beriwal, Surabhi; Strain, Linda S.; Offe, Michael; Wang, Adam S.; Vo, Nghia‐Jack; Gilat Schmidt, Taly; Jordan, Petr (Medical physics (Lancaster), 2022)
Purpose This study developed and evaluated a fully convolutional network (FCN) for pediatric CT organ segmentation and investigated the generalizability of the FCN across image heterogeneities such as CT scanner model protocols and patient age. We also evaluated the autosegmentation models as part of a software tool for patient‐specific CT dose estimation. Methods A collection of 359 pediatric CT datasets with expert organ contours were used for model development and evaluation. Autosegmentation models were trained for each organ using a modified FCN 3D V‐Net. An independent test set of 60 patients was withheld for testing. To evaluate the impact of CT scanner model protocol and patient age heterogeneities, separate models were trained using a subset of scanner model protocols and pediatric age groups. Train and test sets were split to answer questions about the generalizability of pediatric FCN autosegmentation models to unseen age groups and scanner model protocols, as well as the merit of scanner model protocol or age‐group‐specific models. Finally, the organ contours resulting from the autosegmentation models were applied to patient‐specific dose maps to evaluate the impact of segmentation errors on organ dose estimation. Results Results demonstrate that the autosegmentation models generalize to CT scanner acquisition and reconstruction methods which were not present in the training dataset. While models are not equally generalizable across age groups, age‐group‐specific models do not hold any advantage over combining heterogeneous age groups into a single training set. Dice similarity coefficient (DSC) and mean surface distance results are presented for 19 organ structures, for example, median DSC of 0.52 (duodenum), 0.74 (pancreas), 0.92 (stomach), and 0.96 (heart). The FCN models achieve a mean dose error within 5% of expert segmentations for all 19 organs except for the spinal canal, where the mean error was 6.31%. Conclusions Overall, these results are promising for the adoption of FCN autosegmentation models for pediatric CT, including applications for patient‐specific CT dose estimation.